Desenvolvimento de zeólita A com estrutura hierárquica como adsorvente versátil para remoção de íons Cu²⁺, Cd²⁺ e Pb²⁺ em meio aquoso - França, Antonia Mayza de Morais (2024)
Study focuses on optimizing the effectiveness of zeolites in removing metal ions such as Cu²⁺, Cd²⁺ and Pb²⁺, overcoming challenges related to fixed bed column packing and improving analyte access to adsorption pores. Using the hierarchy method, the transport and diffusion properties of zeolites were improved. Hierarchical zeolites were tested for the adsorption of these ions in batch and fixed bed systems. Two Al₂O₃-SiO₂ glass fibers (FB1 and FB2), of different brands. were coated with zeolites and zeolite calcium alginate (AGZA) beads were produced by in-situ coating and ionotropic gelation, respectively. During the initial fiber synthesis process, different temperatures were explored (85, 90, 93, 95 and 100 ºC). Both the fibers and the beads obtained were extensively characterized using different techniques. Results highlighted the excellent performance of fiber samples synthesized at 95 ºC (FB1-95 and FB2-95) in batch adsorption, with a notable preference for Pb²⁺ adsorption. These samples were selected for the fixed bed study, where the observed adsorption order was Pb²⁺ > Cd²⁺ > Cu²⁺. Kinetic, isothermal and thermodynamic models were effective in describing the adsorption behavior in the process, with the LDF model proving adequate to describe the experimental data of adsorption in a fixed bed. For AGZA Beads, batch adsorption experiments showed high performance, especially for Pb²⁺, with better fit to pseudo-second order kinetic and Langmuir isothermal models. Thermodynamic study indicated that the adsorption of Cu²⁺ and Pb²⁺ is exothermic and favored by lower temperatures, while the opposite was observed for Cd²⁺, with all processes being spontaneous. There was a competitive effect between metal ions in the fixed bed adsorption study, with preference for Pb²⁺ adsorption. The recovery of metal ions in AGZA beads was successful using HNO₃. In summary, the results suggest that both AGZA coated fibers and beads have great potential for application in the removal of metal ions from aqueous solutions, contributing to sustainable water treatment methods.